Postexercise muscle glycogen synthesis with combined glucose and fructose ingestion - Wallis, Gareth A; Hulston, Carl J; Mann, Christopher H; Roper, Helen P; Tipton, Kevin D; Jeukendrup, Asker E (Medicine and science in sports and exercise, 2008)
To evaluate the efficacy of using combined glucose and fructose (GF) ingestion as a means to stimulate short-term (4 h) postexercise muscle glycogen synthesis compared to glucose only (G). On two separate occasions, six endurance-trained men performed an exhaustive glycogen-depleting exercise bout followed by a 4-h recovery period. Muscle biopsy samples were obtained from the vastus lateralis muscle at 0, 1, and 4 h after exercise. Subjects ingested carbohydrate solutions containing G (90 g x h(-1)) or GF (G = 60 g x h(-1); F = 30 g x h(-1)) commencing immediately after exercise and every 30 min thereafter. Immediate postexercise muscle glycogen concentrations were similar in both trials (G = 128 +/- 25 mmol x kg(-1) dry muscle (dm) vs GF = 112 +/- 16 mmol x kg(-1) dm; P > 0.05). Total glycogen storage during the 4-h recovery period was 176 +/- 33 and 155 +/- 31 mmol x kg(-1) dm for G and GF, respectively (G vs GF, P > 0.05). Hence, mean muscle glycogen synthesis rates during the 4-h recovery period did not differ between the two conditions (G = 44 +/- 8 mmol x kg(-1) dm x h(-1) vs GF = 39 +/- 8 mmol x kg(-1) dm x h(-1), P > 0.05). Plasma glucose and serum insulin responses during the recovery period were similar in both conditions, although plasma lactate concentrations were significantly elevated during GF compared to G (by approximately 0.8 mmol x L(-1), P < 0.05). Glucose and glucose/fructose (2:1 ratio) solutions, ingested at a rate of 90 g x h(-1), are equally effective at restoring muscle glycogen in exercised muscles during the recovery from exhaustive exercise.